2017
DOI: 10.1155/2017/9765259
|View full text |Cite
|
Sign up to set email alerts
|

Serum Gamma-Glutamyl Transferase and Ferritin Synergistically Associated with the Rate of Chronic Kidney Disease

Abstract: The present study investigated the effects of GGT and SF on the risk of CKD. 1024 participants (436 men and 588 women) were divided into three groups according to GGT and SF levels: group 1 (both GGT and SF not in the fourth quartile), group 2 (only GGT or SF in the fourth quartile), and group 3 (both GGT and SF in the fourth quartile). The risks of CKD in different levels of GGT and SF and in groups 2-3 compared with group 1 were analyzed by multiple logistic regression. GGT or SF in the highest quartile was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Compared with the normal-ferritin group, the adjusted odds ratios (95% CI) for CKD of the high-ferritin group were 1.57 (1.01-2.44) in men and 1.06 (0.38-2.96) in women, which suggested that SF was associated with a higher prevalence risk of CKD in men, but not in women in Korea. Chen et al 13 found that in communitydwelling Chinese, SF in the highest quartiles was associated with increased risk of CKD, such an association was dependent on confounding factors. When gamma-glutamyl transferase and SF were analysed in combination, the rate of CKD increased.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared with the normal-ferritin group, the adjusted odds ratios (95% CI) for CKD of the high-ferritin group were 1.57 (1.01-2.44) in men and 1.06 (0.38-2.96) in women, which suggested that SF was associated with a higher prevalence risk of CKD in men, but not in women in Korea. Chen et al 13 found that in communitydwelling Chinese, SF in the highest quartiles was associated with increased risk of CKD, such an association was dependent on confounding factors. When gamma-glutamyl transferase and SF were analysed in combination, the rate of CKD increased.…”
Section: Discussionmentioning
confidence: 98%
“…Some published studies have reported that SF is associated with the incidence of CKD. 12,13 However, most of these studies were either cross-sectional or conducted in general populations with normal SF concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Even though it is well-known that iron deficiency is the result of CKD, whether iron status is associated with the risk of CKD in general population is unclear. Several studies previously investigated the associations between iron status and CKD/renal function in general population with insosistent results (27)(28)(29)(30)(31), and most of them generally focused on the markers of iron with a single type. We found that participants in the highest tertile of SF had increased risk of CKD than those in the lowest tertile, which was comparable with previous studies (27,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested that GGT is an independent predictor of mortality in patients with stage 4-5 chronic kidney disease [26]. Some previous studies have suggested an association of serum GGT with development and progression of CKD [27][28][29] although some studies have suggested that in some ethnic groups this association is confounded by other factors such as body mass index, life style factors, lipids, smoking and heavy alcohol intake [28,30]. This positive association of high baseline concentrations of GGT with poor renal outcomes may indicate that the serum levels of this enzyme can be used as a surrogate marker of risk for poor renal outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism linking GGT and progression of CKD is unclear and will need to be further studied although oxidative stress and in ammation in synergy with serum ferritin have been suggested [27].…”
Section: Discussionmentioning
confidence: 99%